The Obesity Epidemic: From the Environment to Epigenetics – Not Simply a Response to Dietary Manipulation in a Thermoneutral Environment - Symonds, Michael E.; Sebert, Sylvain; Budge, Helen (Frontiers in Genetics, 2011)
The prevalence of obesity continues to increase particularly in developed countries. To establish the primary mechanisms involved, relevant animal models which track the developmental pathway to obesity are required. This need is emphasized by the substantial rise in the number of overweight and obese children, of which a majority will remain obese through adulthood. The past half century has been accompanied with unprecedented transitions in our lifestyle. Each of these changes substantially contributes to enhancing our capacity to store energy into adipose tissues. The complex etiology of adiposity is critical as a majority of models investigating obesity utilize a simplistic high-fat/low-carbohydrate diet, fed over a short time period to comparatively young inbred animals maintained in fixed environment. The natural history of obesity is much more complex involving many other mechanisms and this type of challenge may not be the optimal experimental intervention. Such processes include changes in adipose tissue composition with time and the transition from brown to white adipose tissue. Brown adipose tissue, due its unique ability to rapidly produce large amounts of heat could have a pivotal role in energy balance and is under epigenetic regulation mediated by the histone H3k9-specific demethylase Jhdma2a. Furthermore, day length has a potential role in determining endocrine and metabolic responses in brown fat. The potential to utilize novel models and interventions across a range of animal species in adipose tissue development may finally start to yield sustainable strategies by which excess fat mass can, at last, be avoided in humans.